"On water" direct catalytic vinylogous Henry (nitroaldol) reactions of isatins for the efficient synthesis of isoxazole substituted 3-hydroxyindolin-2-ones1. Issue 6 (8th June 2015) - Zhang, Yong; Wei, Biao-Wen; Lin, Hui; Zhang, Ling; Liu, Jin-Xiang; Luo, Hai-Qing; Fan, Xiao-Lin
<x xml:space="preserve">Abstract</x> An efficient "on water"-promoted direct catalytic vinylogous Henry reaction is described, giving products in excellent yields and diastereoselectivities.